2020
DOI: 10.4103/ijmr.ijmr_2987_20
|View full text |Cite
|
Sign up to set email alerts
|

Gargle lavage as a viable alternative to swab for detection of SARS-CoV-2

Abstract: Background & objectives: Nasopharyngeal and oropharyngeal swab (NPS and OPS) collection is widely accepted as the preferred method for obtaining respiratory samples. However, it has certain disadvantages which may be overcome by gargling. The primary objective of this study was to assess agreement between gargle lavage and swab as an appropriate respiratory sample for the detection of SARS-CoV-2. The secondary objective was to assess the patient acceptability of the two sampling methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…For each specimen type, in addition to data on test performance, we extracted data for factors likely to affect test performance, as detailed below. Data on throat or gargle washes were not included in this meta-analysis ( 12 , 13 ). We obtained the limit of detection (LOD) from studies by direct report within the study when available, and otherwise by manufacturer claims (package insert if available; Table S1 in the supplemental material lists how LOD was ascertained by study).…”
Section: Methodsmentioning
confidence: 99%
“…For each specimen type, in addition to data on test performance, we extracted data for factors likely to affect test performance, as detailed below. Data on throat or gargle washes were not included in this meta-analysis ( 12 , 13 ). We obtained the limit of detection (LOD) from studies by direct report within the study when available, and otherwise by manufacturer claims (package insert if available; Table S1 in the supplemental material lists how LOD was ascertained by study).…”
Section: Methodsmentioning
confidence: 99%
“…Posterior oropharyngeal saliva and gargle lavage have been reported to show promising performance compared to nasopharyngeal and oropharyngeal swabs for the detection of COVID-19 [10,11,[17][18][19] and other respiratory viruses [20]. Goldfarb et al (2020) found that self-collected gargle specimens are more sensitive and more acceptable than saliva samples in outpatient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The following primers were used: SCoV2 QPCR FP, 5′- TGGACCCCAAAATCAGCGAA ; SCoV2 QPCR RP, 5′- TCGTCTGGTAGCTCTTCGGT ; RP II FP, 5′- GCACCACGTCCAATGACAT ; RP II RP, 5′- GTCGGCTGCTTCCATAA ; RP FP, 5′- AGATTTGGACCTGCGAGCG ; RP RP, 5′- GAGCGGCTGTCTCCACAAGT ; LAMP2A FP, 5′- TATGTGCAACAAAGAGCAGAC3 ; LAMP2A RP, 5′- AAGCCAGCAACACTAGAATAAG3 ; LAMP2B FP: 5′- TATGTGCAACAAAGAGCAGAC3 , LAMP2B RP, 5′- TGCCAATTACGTAAGCAATCA . TaqMan-based RT-qPCR was done as described earlier, by following the protocol suggested by the CDC, USA ( 60 ). The following primers and probes were used: N1 FP, 5′- GACCCCAAAATCAGCGAAAT ; N1 RP, 5′- TCTGGTTACTGCCAGTTGAATCTG ; N1 probe, 5′-FAM- ACCCCGCATTACGTTTGGTGGACC -BHQ1; N2 FP, 5′- TTACAAACATTGGCCGCAAA ; N2 RP, 5′- GCGCGACATTCCGAAGAA ; N2 probe, 5′-FAM- ACAATTTGCCCCCAGCGCTTCAG -BHQ1; RP FP, 5′- AGATTTGGACCTGCGAGCG ; RP RP, 5′- GAGCGGCTGTCTCCACAAGT ; RP probe, 5′-FAM- TTCTGACCTGAAGGCTCTGCGCG -BHQ1.…”
Section: Methodsmentioning
confidence: 99%